BREVES CONSIDERAÇÕES SOBRE A USUCAPIÃO EXTRAJUDICIAL REALIZADA NO CARTÓRIO DE REGISTRO DE IMÓVEIS (Reflection and Critique Law Magazine, 2020)
The purpose of this paper is to analyze one of the great novelties of the Code of Civil Procedure, Law 13.105, extrajudicial misappropriation, since it made possible the processing of this modality of acquisition of property before the Property Registry. To better develop the subject, the study of possession begins, tracing brief of conceptualization until the loss of possession. Next, will be studied the usucaption, opportunely in which will be discussed on the concept, requirements, species and their effects. Specifically addressing the subject of work, extrajudicial misappropriation will be considered, as well as the legal feasibility of this modality in the Brazilian legal system and the castorian reality. Thus, in order to demonstrate the functionality of extrajudicial misappropriation carried out in the notary's office, a study of laws and doctrines will be used, which will certainly provide a clear and didactic approach on this subject so important nowadays.